Estimating the top altitude of optically thick ice clouds from thermal infrared satellite observations using CALIPSO data - Patrick Minnis; Chris R. Yost; Sunny Sun‐Mack; Yan Chen (Geophysical Research Letters)
The difference between cloud‐top altitude Ztop and infrared effective radiating height Zeff for optically thick ice clouds is examined using April 2007 data taken by the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) and the Moderate‐Resolution Imaging Spectroradiometer (MODIS). For even days, the difference ΔZ between CALIPSO Ztop and MODIS Zeff is 1.58 ± 1.26 km. The linear fit between Ztop and Zeff, applied to odd‐day data, yields a difference of 0.03 ± 1.21 km and can be used to estimate Ztop from any infrared‐based Zeff for thick ice clouds. Random errors appear to be due primarily to variations in cloud ice‐water content (IWC). Radiative transfer calculations show that ΔZ corresponds to an optical depth of ∼1, which based on observed ice‐particle sizes yields an average cloud‐top IWC of ∼0.015 gm−3, a value consistent with in situ measurements. The analysis indicates potential for deriving cloud‐top IWC using dual‐satellite data.